2007
DOI: 10.1007/s11270-007-9409-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper on the Sorption of Phthalate Esters to Yellow River Sediment

Abstract: The sorption of hydrophobic organic pollutants on soils or sediments has been widely studied. However, more attention in the previous studies has been paid to sorption mechanism and effects of relevant environmental factors, few studies were reported on effects of heavy metals on the sorption of hydrophobic organic pollutants. In this paper, sorption of phthalate esters (diethyl phthalate, DEP, and di-n-butyl phthalate, DnBP) and copper on the Yellow River sediment was investigated with particular attention to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…5A and B). Because PAEs are hydrophobic contaminants and readily adsorbed and fixed by sediment OM, local source transport and mixing processes are factors (Xu et al, 2007;Zeng et al, 2008;Liu et al, 2010;Magdouli et al, 2013;Zheng et al, 2014). In addition, no correlation was found between the Σ 6 PAEs and pH of the sediments (Fig.…”
Section: Relationships Between Paes and Sediment Physicochemical Propmentioning
confidence: 98%
See 1 more Smart Citation
“…5A and B). Because PAEs are hydrophobic contaminants and readily adsorbed and fixed by sediment OM, local source transport and mixing processes are factors (Xu et al, 2007;Zeng et al, 2008;Liu et al, 2010;Magdouli et al, 2013;Zheng et al, 2014). In addition, no correlation was found between the Σ 6 PAEs and pH of the sediments (Fig.…”
Section: Relationships Between Paes and Sediment Physicochemical Propmentioning
confidence: 98%
“…Several studies have focused on the concentrations and distribution of PAEs in lakes and large rivers, but studies on suburban river networks are limited (Yuan et al, 2002;Xu et al, 2007;Sun et al, 2013;Zheng et al, 2014). Zeng et al (2008) reported that the Σ 16 PAEs concentrations in urban lake sediments ranged from 2.3 to 74.9 mg kg −1 dry weight (dw) with a mean concentration of 20.8 mg kg −1 in Guangzhou, South China.…”
Section: Introductionmentioning
confidence: 99%
“…The surfacial sediments (SSs) and natural surface coating samples (NSCSs) are often considered as main carriers and potential sources of both organic and inorganic pollutants in aquatic environments [12][13][14]. They are playing a significant role in the adsorption of pollutants owing to their abundant internal surface area and high sorption intensity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Mn oxides, Fe oxides and organic materials (OMs) are most important components in SSs [11,12]. They play important roles in controlling the adsorption of organic and inorganic contaminants, with different contribution to the adsorption [13][14][15]. The various sediment components may contribute independently to the sorption of organic pollutants; however, interactions between components may also take place [16].…”
Section: Introduction Atrazinementioning
confidence: 99%